Reinforced Concrete Beams with Opening Strengthened using CFRP Sheets - Ali, Noorwirdawati; Abdul Hamid, Noor Azlina; Salleh, Norhafizah; Abdullah, Siti Radziah; Jamellodin, Zalipah (UTHM, 2019)
This study explores the behavior of reinforced concrete beam with opening strengthened using CFRP sheets. The beams were deficient in bending and under-reinforced in order for the beams to fail in bending. Loaddeflection behavior and strain profile were observed besides the crack pattern and modes of failure. A total of five (5) beams were casted and tested. One (1) beam was treated as control specimen, two (2) beams were reinforced concrete beams with square and circular opening respectively while the other two (2) beams were reinforced concrete beams with square and circular opening strengthened using CFRP sheets. For the strengthened beams, they were wrapped at three sides (U-wrap) of the beams with CFRP sheets. From the experimental results, it is observed that all beams fail in bending as expected. Beam with circular opening (un-strengthened) recorded the lowest ultimate load with 25.7 kN, a decreased for about 6.4% compared to control specimen. On the other hand, beams with circular opening strengthened using CFRP sheets recorded the highest ultimate load of 30.7 kN, which is an increased for about 11.9% compared to control specimen. The conclusion that can be drawn from this study is CFRP sheets can be used to increase the ultimate load of beam with the presence of opening.